Solution conformation of several free tRNALeu species from bean, yeast and Escherichia coli and interaction of these tRNAs with bean cytoplasmic Leucyl-tRNA synthetase. A phosphate alkylation study with ethylnitrosourea. - Dietrich, A (1990)
The solution conformation of eight leucine tRNAs from Phaseolus vulgaris, baker's yeast and Escherichia coli, characterized by long variable regions, and the interaction of four of them with bean cytoplasmic leucyl-tRNA synthetase were studied by phosphate mapping with ethylnitrosourea. Phosphate reactivities in the variable regions agree with the existence of RNA helices closed by miniloops. At the junction of these regions with the T-stem, phosphate 48 is strongly protected, in contrast to small variable region tRNAs where P49 is protected. The constant protection of P22 is another characteristics of leucine tRNAs. Conformational differences between leucine isoacceptors concern the anticodon region, the D-arm and the variable region. In several parts of free tRNALeu species, e.g. in the T-loop, phosphate reactivities are similar to those found in tRNAs of other specificities, indicating conformational similarities among tRNAs. Phosphate alkylation of four leucine tRNAs complexed to leucyl-tRNA synthetase indicates that the 3'-side of the anticodon stem, the D-stem and the hinge region between the anticodon and D-stems are in contact with the plant enzyme.